Fractional Version of Hermite-Hadamard and Fejér Type Inequalities for a Generalized Class of Convex Functions - Lei Geng; Muhammad Shoaib Saleem; Kiran Naseem Aslam; Rahat Bano (Journal of Function Spaces, 2022)
In the present paper, we deal with some fractional integral inequalities for strongly reciprocally p,h-convex functions. We established fractional version of Hermite-Hadamard and Fejér type inequalities for strongly reciprocally p,h-convex functions. Our results extend and generalize many exiting results of literate.